Edukasi Program Latihan Pada Penderita Osteoartritis Lutut di Posyandu Lansia Mawar Setabelan - Erica Dimashanda; Wijianto Wijianto; Yusuf Arianto (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2024)
Osteoarthritis (OA) is a chronic, degenerative disease that attacks the joints and their tissues, primarily causing progressive damage to the articular cartilage and, subsequently, to the subchondral bone and surrounding synovial structures. Knee osteoarthritis commonly affects elderly patients and is a major cause of disability worldwide. The purpose of this activity is so that the public can find out about exercise programs that can be carried out to reduce complaints in OA sufferers. Counseling is carried out using the lecture method by distributing leaflets, implementing training programs, and asking questions. The data collection method in this research is by using pre-test and post-test. Based on the data obtained, there were quite significant changes in pre-test and post-test scores. The average correct answer on the pre-test questions was 4.9 (49%) increasing to 7.6 (76%) on the post-test questions. Thus, there was an increase in correct answers made by participants by 2.7 points (27%). So it can be concluded that participants in counseling activities experienced an increase in understanding of the osteoarthritis material that was presented.